Breast rhagades in nursing and non lactating women: A gordian knot to loose by the aid of a phytocosmetical formulation - Lorenzo Martini (Our Dermatology Online, 2016)
We have tried to solve an everlasting problem inherent the treatment of breast rhagades in woman, since mammary gland proposes several troubles: 1) drug penetration through the mammal areola epidermis is the quickest, after the one through eye conjunctive and so whichever chemical or natural substance (for instance triterpenes or cyanhydrin or amygdalin present in sweet almond oil) may be retrieved in human milk and blood after few minutes) 2) Milk is suckled by the bébé and it is supposed that whichever remedy against breast rhagades should be applied topically before and after each feeding and thus most of the substances included in the remedy passes into human milk. 3) Mammary gland is victim of the aggression of manifold germs and bacteria from the bébés' mouth. There is an avalanche of cosmetic and pharmaceutical commodities that always fail in some of the aforesaid corollaries. Our gélée tends to comply all the prerequisites and we have demonstrated this hypothesis.